Determination of Service Innovation, Attitude, and Satisfaction in Adopt Use of Sharia Fintech - Wahid Wachyu Adi Winarto (Faculty of Economics, Universitas Internasional Batam, 2022)
Purpose - The purpose of this paper is to analyze the determination of service innovation, attitudes and user satisfaction on the intention to use Sharia FinTech repeatedly. Research Method – Using a survey approach to users and prospective users of Sharia FinTech services in the research area, the research sample was 195 respondents and then analyzed by path analysis using the Smart PLS analysis tool. Findings - The authors find evidence that service innovation has an impact on perceived usefulness and perceived ease of use. Perceived ease of use, perceived usefulness both affect the attitude of service users. Attitude will have an impact on user satisfaction, from there users of sharia FinTech services will repeat their use because they feel satisfied. Implication – The increase in service user needs to be considered by developers of sharia FinTech systems, what must be done is to innovate sharia FinTech services in terms of increasing the ease of fullness and fullness of use so that they are developed according to the wishes or needs of the service.